Managing household finances: How engaging in financial management activities relates to the experiential well-being of Americans - Thomas Korankye; Blain Pearson (Journal of Risk and Financial Management, 2023)
This study examines how engagement in financial management activities influences well-being using nationally representative data (N = approximately 30,000) from the U.S. Bureau of Labor Statistics' American Time Use Survey and its associated Well-Being Modules. The current study estimates ordered probit models for several measures of experiential well-being, which consider how meaningful an activity is for a household and how happy, sad, tired, in pain, and stressed respondents felt during the activity. Controlling for a standard set of demographic and socioeconomic factors, the econometric results indicate that households report lower utility gains (lower happiness, greater sadness, and higher stress) when engaging in financial management activities relative to other activities. Furthermore, the results suggest increases in household time allocated toward performing financial management activities is associated with a lower (higher) likelihood of being very happy (very stressed) compared to other activities. The findings strongly indicate that households perceive financial management activities as vexing, reinforcing the need for financial stewardship support to promote household well-being.
Keywords: 650; American Time Use Survey; experiential well-being; financial management; household and personal finances